(untitled) (CIPEEX, 2025)
Street running is a poorly investigated modality due to the limitations of in-locus measurements and the diversity of its practitioners. Regarding blood pressure, there are no published studies with different training methodologies that are conducted on-site. The objective of the present study is to evaluate the subacute responses of blood pressure (BP) in healthy young adults who practice street running, after a session of high-intensity interval running and a session of moderate-intensity continuous running, and a control session. This is a cross-sectional study conducted with 10 street runners, subjected to 3 protocols: continuous aerobic (PAC); high-intensity interval (PIAI); and control (PC). Hemodynamic measurements were taken before, immediately after, and every 10 minutes until 40 minutes after the completion of the protocols. Results: Significant elevation of SBP immediately after the running session, both in PAC and PIAI, when compared to the pre-exercise moment, but significantly higher in the PIAI group. These responses were not exaggerated, returning to baseline values in subsequent moments (without significance in intra- and intergroup analysis). DBP showed a significant increase in both exercise protocols immediately post-exercise and 20 minutes after, but to the same extent. At the 40-minute mark, the PIAI group maintained a significantly higher DBP than the PAC group. Conclusion: The runners exhibited higher blood pressure values immediately after both exercise sessions in a similar magnitude, but did not experience post-exercise hypotension in either protocol.